Towards microalgal triglycerides in the commodity markets - Benvenuti, Giulia (Biotechnol Biofuels, 2017)
BACKGROUND: Microalgal triglycerides (TAGs) hold great promise as sustainable feedstock for commodity industries. However, to determine research priorities and support business decisions, solid techno-economic studies are essential. Here, we present a techno-economic analysis of two-step TAG production (growth reactors are operated in continuous mode such that multiple batch-operated stress reactors are inoculated and harvested sequentially) for a 100-ha plant in southern Spain using vertically stacked tubular photobioreactors. The base case is established with outdoor pilot-scale data and based on current process technology. RESULTS: For the base case, production costs of 6.7 € per kg of biomass containing 24% TAG (w/w) were found. Several scenarios with reduced production costs were then presented based on the latest biological and technological advances. For instance, much effort should focus on increasing the photosynthetic efficiency during the stress and growth phases, as this is the most influential parameter on production costs (30 and 14% cost reduction from base case). Next, biological and technological solutions should be implemented for a reduction in cooling requirements (10 and 4.5% cost reduction from base case when active cooling is avoided and cooling setpoint is increased, respectively). When implementing all the suggested improvements, production costs can be decreased to 3.3 € per kg of biomass containing 60% TAG (w/w) within the next 8 years. CONCLUSIONS: With our techno-economic analysis, we indicated a roadmap for a substantial cost reduction. However, microalgal TAGs are not yet cost efficient when compared to their present market value. Cost-competiveness strictly relies on the valorization of the whole biomass components and on cheaper PBR designs (e.g. plastic film flat panels). In particular, further research should focus on the development and commercialization of PBRs where active cooling is avoided and stable operating temperatures are maintained by the water basin in which the reactor is placed. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13068-017-0873-2) contains supplementary material, which is available to authorized users.